2014
DOI: 10.3389/fnhum.2014.00140
|View full text |Cite|
|
Sign up to set email alerts
|

The role of action representations in thematic object relations

Abstract: A number of studies have explored the role of associative/event-based (thematic) and categorical (taxonomic) relations in the organization of object representations. Recent evidence suggests that thematic information may be particularly important in determining relationships between manipulable artifacts. However, although sensorimotor information is on many accounts an important component of manipulable artifact representations, little is known about the role that action may play during the processing of sema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 70 publications
4
16
0
Order By: Relevance
“…The magnitude of this advantage related to individual performance in artifact action knowledge, and both abilities rely on the integrity of the left posterior temporal cortex. The present findings are consistent with previous studies showing that thematic relations rely on the posterior temporal cortex (Kalénine et al, 2009; Mirman & Graziano, 2012b; Sass et al, 2009; Schwartz et al, 2011; Tsagkaridis et al, 2014). They further provide novel insights into the functional role of this region in thematic knowledge, and suggest that the close association between thematic relations for artifacts and action representations may reflect their common dependence on visual motion and manipulation information.…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…The magnitude of this advantage related to individual performance in artifact action knowledge, and both abilities rely on the integrity of the left posterior temporal cortex. The present findings are consistent with previous studies showing that thematic relations rely on the posterior temporal cortex (Kalénine et al, 2009; Mirman & Graziano, 2012b; Sass et al, 2009; Schwartz et al, 2011; Tsagkaridis et al, 2014). They further provide novel insights into the functional role of this region in thematic knowledge, and suggest that the close association between thematic relations for artifacts and action representations may reflect their common dependence on visual motion and manipulation information.…”
Section: Resultssupporting
confidence: 94%
“…In the light of previous findings (Kalenine et al 2009; Tsagkaridis et al 2014), we originally hypothesized that thematic relations between manipulable artifacts specifically rested upon artifact action knowledge. Following from this, we investigated the selective relationship between performance in the identification of thematic relations for manipulable and non-manipulable artifact concepts and performance in artifact action knowledge (gesture recognition) in patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This idea that types of thematic relations play differential roles in processing items from particular categories is supported by existing empirical research. Tsagkaridis, Watson, Jax, and Buxbaum (2014) demonstrated that when processing manipulable artifact concepts (e.g., Bwine bottle^), participants preferred action-based thematic relations (e.g., Bcorkscrew^; referred to as argument relations in the present research) to thematic relations in which the objects do not directly interact with one another (e.g., Bcheese^; referred to as coordinate relations in the present research). Whether the centrality of certain types of thematic relations has an impact on human processing of a wide range of categories remains to be examined (e.g., is it easier for people to process concepts in locative relations if those concepts are foods or animals than if they are instruments?…”
Section: Resultsmentioning
confidence: 49%